2022
DOI: 10.1007/s12602-022-09969-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oral Probiotics in Amelioration of Immunological and Inflammatory Responses on Experimentally Induced Acute Diverticulitis

Abstract: Acute diverticulitis is inflammation of a colon diverticulum; it represents a major cause of morbidity and mortality. The alteration of gut microbiota contributes to the promotion of inflammation and the development of acute diverticulitis disease. Probiotics can modify the gut microbiota, so they are considered a promising option for managing diverticulitis disease. This study aimed to investigate the potential protective effect of probiotics, alone or in combination with amoxicillin, on the experimentally in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Govindarajah et al (2014) reported that; there was a significant decrease in serum CRP levels in response to co-amoxicillin gentamycin therapy in a case of appendiceal or acute colonic pathology associated with gall bladder cholecystitis. Similarly, Seaton et al (2020) and Soliman et al (2022) pointed to the role of amoxicillin therapy in decreasing serum CRP levels. Isaacs and Sartor (2004) agreed with these results demonstrating that; antibiotics may decrease bacterial tissue invasion, impair bacterial attachment, decrease bacterial translocation and prevent systemic dissemination.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Govindarajah et al (2014) reported that; there was a significant decrease in serum CRP levels in response to co-amoxicillin gentamycin therapy in a case of appendiceal or acute colonic pathology associated with gall bladder cholecystitis. Similarly, Seaton et al (2020) and Soliman et al (2022) pointed to the role of amoxicillin therapy in decreasing serum CRP levels. Isaacs and Sartor (2004) agreed with these results demonstrating that; antibiotics may decrease bacterial tissue invasion, impair bacterial attachment, decrease bacterial translocation and prevent systemic dissemination.…”
Section: Discussionmentioning
confidence: 97%
“…( 2020 ) and Soliman et al . ( 2022 ) pointed to the role of amoxicillin therapy in decreasing serum CRP levels. Isaacs and Sartor ( 2004 ) agreed with these results demonstrating that; antibiotics may decrease bacterial tissue invasion, impair bacterial attachment, decrease bacterial translocation and prevent systemic dissemination.…”
Section: Discussionmentioning
confidence: 99%